The Influence of Audit Fees and Auditor Assessment on Financial Decision Making in Banking Companies at the Indonesian Stock Exchange (2020-2024) - Nurul Habibah; Any Eliza; Rosydalina Putri (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of audit fees and auditor assessments on financial decision-making in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The background of the study is based on the importance of reliable and timely financial information as a basis for decision-making by management and investors, especially in the banking sector which has strict regulations and high transaction complexity. The study uses an associative quantitative approach with secondary data from annual reports and independent auditor reports. The sample was determined using a purposive sampling method, with logistic regression analysis techniques. The results of the study indicate that audit fees do not significantly influence financial decision-making (H1 is rejected), while auditor assessment also does not significantly influence financial decision-making (H2 is rejected). Simultaneously, audit fees and auditor assessment do not show a significant influence on financial decision-making. This finding indicates that in the banking context at the IDX, variations in audit fees and auditor assessment indicators are not strong enough to influence financial decisions compared to other more dominant factors such as fundamental financial performance conditions and internal and external monitoring mechanisms. This study provides empirical contributions by enriching evidence regarding the role of audit fees and auditor assessments in financial decision-making in the banking sector in Indonesia and provides input for regulators, bank management, and the public accounting profession regarding the importance of ensuring that the added value of audits is substantively reflected in the reporting and decision-making process.